Green Product Purchase Intention with Green Campaign Mediation Self Determination Theory Concept - Azizah, Yuliatin; Azim, Fauzan; Ambarwati, Lucky (Image : Jurnal Riset Manajemen, 2024)
Marketing of green products as environmentally friendly products still experiences obstacles in Jember City. This is because the community is less responsive to environmentally friendly products. Research is needed on consumer behavior related to motivation and a green campaign is given, namely an environmental campaign as an effort to promote environmentally friendly products, practices and policies to optimize the intention to purchase green products. This study contributes a deeper understanding of motivation and environmental campaigns to build green product purchase intentions, with the Self-Determination Theory (SDT) approach. SDT is used to understand motivation broadly with 6 complete continua, namely amotivation, external regulation, introjected regulation, identified regulation, integrated regulation and intrinsic motivation and integrates SDT with the role of the campaign as a mediator. A total of 210 respondents were analyzed using the PLS Equation Model Structure with the WrapPLS 7.0 program analysis tool with the results of Self-determination theory having a very strong model for the intention to purchase green products and green campaigns. The campaign as a mediator has no effect. The emphasis on identified regulation and intrinsic motivation is to provide values of awareness and pleasure by protecting the environment to prove that green products are not just a company's claim to gain profit but an effort to save the earth from damage.